Certain Non-Linear Differential Polynomials Sharing 1-Points With Finite Weight: Abhijit Banerjee, Sujoy Majumder - Team, Support (Thai Journal of Mathematics, 2012)
We employ the notion of weighted sharing of values to study the uniqueness of meromorphic functions when certain non-linear differential polynomials share the same 1-points. As a consequence of the main result we improve and supplement a result of Lahiri-Sarkar [I. Lahiri, A. Sarkar, Nonlinear differential polynomials sharing 1-points with weight two, Chinese J. Contemp. Math. 25 (3) (2004) 325–334] as well as a recent result of Zhang-Lin [X.Y. Zhang, W.C. Lin, Uniqueness and value sharing of entire functions, J. Math. Anal. Appl. 343 (2008) 938–950].